2018
DOI: 10.1159/000489564
|View full text |Cite
|
Sign up to set email alerts
|

Galangin Induces Apoptosis in MCF-7 Human Breast Cancer Cells Through Mitochondrial Pathway and Phosphatidylinositol 3-Kinase/Akt Inhibition

Abstract: Aims: The study aimed to investigate the molecular mechanism of inhibition of proliferation and apoptosis induction by galangin against MCF-7 human breast cancer cells. Methods: Cell Counting Kit-8 assay was used to assess cell viability and flow cytometry was used to detect cell apoptosis. The expression level of apoptosis-related proteins (cleaved-caspase-9, cleaved-caspase-8, cleaved-caspase-3, Bad, cleaved-Bid, Bcl-2, Bax, p-phosphatidylinositol 3-kinase [PI3K], and p-Akt) and cell cycle-related proteins (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 49 publications
(58 reference statements)
5
23
0
Order By: Relevance
“…Additionally, we also explored the effect of PI3K/AKT pathway on tumor cell growth and apoptosis. From the previous studies, 22 25 we concluded that the activation of the PI3K/AKT pathway can increase the proliferation of tumor cells and inhibit the apoptosis of cells, which is consistent with our study. In our study, we added PI3K inhibitor or PI3K activator to explore the effect of PI3K/AKT pathway.…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, we also explored the effect of PI3K/AKT pathway on tumor cell growth and apoptosis. From the previous studies, 22 25 we concluded that the activation of the PI3K/AKT pathway can increase the proliferation of tumor cells and inhibit the apoptosis of cells, which is consistent with our study. In our study, we added PI3K inhibitor or PI3K activator to explore the effect of PI3K/AKT pathway.…”
Section: Discussionsupporting
confidence: 92%
“…It can significantly inhibit the proliferation of TNBC cell lines (MDA-MB-231, BT-549, HCC70, and HCC1806) compared with non-tumorigenic BC lines (MCF-10A and AG11132) through downregulating the expression of CDK1 [159]. Moreover, Galangin, another plant anticancer compound, inhibits the survival of MCF-7 cells and induces apoptosis by downregulating CDK1, CDK2, and CDK4, leading to cell-cycle arrest [160]. The 5,7-dihydroxy-2-[4 -hydroxy-3 -(methoxymethyl)phenyl]-6-C-β-glucopyranosyl flavone (from Urginea indica bulb) induces G0/G1 arrest and apoptosis, as well as inhibits angiogenesis in BC cells through targeting CDK1 and CDK6 [161].…”
Section: The Novel Cdk Inhibitors In Bcmentioning
confidence: 99%
“…Cell apoptosis is induced by multiple signaling pathways, including the Akt signaling pathway which has a central role in cell apoptosis. Therefore, anticancer drugs often induce cancer apoptosis through inhibiting the AKT signaling pathway (39,40). It has been reported that Pris is a potential anticancer drug that can induce apoptosis in pancreatic cancer cells and colorectal cancer cells (15,41).…”
Section: Discussionmentioning
confidence: 99%